Scaffolding Strategy Based-Writing Instruction to Promote Students’ Grammar Mastery in Written Communication - Saputri, Vike Aprilianin Marwintaria; Wibawa, Resdhi; Agustin, Drian; Kosasih, Ananda; Enrico, Albert (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
The purposes of this study are to find out the difference of the students’ grammar mastery in written communication after the implementation of scaffolding strategy based - writing instruction and to describe the students’ response to scaffolding strategy based - writing instruction in writing class. The sample is twenty students of the third semester Buddhist Communication Science Department in the academic year 2022-2023. This research is quantitative and qualitative by using one group pre-test posttest design. The instruments are writing test, questionnaire, and interview. The result of data analysis shows that there is a significant difference in the students’ grammar mastery in written communication. The result of the questionnaire shows that the students give the positive response towards applying scaffolding strategy based - writing instruction in writing class. The conclusion of this present study, after the students are given scaffolding strategy based – writing instruction, along with the improvement in writing ability, the students’ grammar mastery in written communication improves significantly.